2021
DOI: 10.24815/siele.v8i3.19988
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Thai elementary students’ English and maintaining Thainess using localized materials: Two putative confronting forces

Abstract: In Thailand, concerns over the imperative need to improve its citizens’ English proficiency and the unsatisfactory English learning outcomes have long been present. In addition, ongoing globalization has raised another concern that Thainess is being eroded due to external influences. This study attempted to compromise these two seemingly conflicting forces by enhancing Thai students’ global English and maintaining local Thainess associated with three regions of Thailand. First, a set of instructional innovatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similarly, a study conducted in Iran indicated that the incorporation of L1 culture into learning materials can improve students' language proficiency as well as facilitate the learning process and increase their interests and motivation in L2 cultural learning (Meraji & Zamanian, 2014). In the Thai context, earlier studies have shown that the use of localized materials (e.g., temples and folktales) can promote students' learning of cultural aspects and develop their sense of cultural belonging and appreciation (Kanoksilapatham & Channuan, 2018), enhance students' knowledge of local Thainess and the English language (Kanoksilapatham & Suranakkharin, 2021), and facilitate the learning of knowledge from a folktale (Boonyananta & Imsamraan, 2022). These imply that the incorporation of ethnic cultures into foreign or second language materials is vital since teachers can utilize those materials to engage and maximize students' learning of languages and cultures, promote their identities, and provide ethnic cultural learning for students along with its multicultural education worldwide.…”
Section: Cultures and Materials Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study conducted in Iran indicated that the incorporation of L1 culture into learning materials can improve students' language proficiency as well as facilitate the learning process and increase their interests and motivation in L2 cultural learning (Meraji & Zamanian, 2014). In the Thai context, earlier studies have shown that the use of localized materials (e.g., temples and folktales) can promote students' learning of cultural aspects and develop their sense of cultural belonging and appreciation (Kanoksilapatham & Channuan, 2018), enhance students' knowledge of local Thainess and the English language (Kanoksilapatham & Suranakkharin, 2021), and facilitate the learning of knowledge from a folktale (Boonyananta & Imsamraan, 2022). These imply that the incorporation of ethnic cultures into foreign or second language materials is vital since teachers can utilize those materials to engage and maximize students' learning of languages and cultures, promote their identities, and provide ethnic cultural learning for students along with its multicultural education worldwide.…”
Section: Cultures and Materials Developmentmentioning
confidence: 99%
“…In materials development, communicative and authentic aspects should be considered since they enable the teacher to select specific types of materials and specifications to match students' learning conditions, connect the materials to their interests, help them experience authentic language use, make learning more engaging, and gain more knowledge from the tasks (McDonough et al, 2013). These concepts can be seen from the use of materials development based on ethnic folktales of Makassar for students' learning of ethnic cultures in Indonesia (Batari et al, 2015), learning L1 culture in second language materials in Iran (Meraji & Zamanian, 2014), using localized materials development to enhance students' English and knowledge of Thainess (Kanoksilapatham & Suranakkharin, 2021), and designing teaching and learning activities based on a folktale for youths (Boonyananta & Imsamraan, 2022) in the Thai context. The results of these studies showed positive outcomes related to students' needs, knowledge of cultures, and attitudes towards learning.…”
Section: Materials Development and Students' Learningmentioning
confidence: 99%